(untitled) (Swiss Medical Weekly, 2012)
OBJECTIVE: Whether underlying chronic respiratory diseases are susceptible factors for symptomatic episodes, which lead to primary-level care, in association with air pollutant exposures is unknown. We evaluated and compared association lag structures between daily ambient levels of nitrogen dioxide (NO2) and total suspended particulates (TSP) and respiratory symptom-related doctor visits in adults with different patterns of underlying chronic respiratory disease. METHODS: In a time-stratified case-crossover analysis nested within a diary panel study, 459 Swiss adult participants with asthma, chronic bronchitis, chronic obstructive pulmonary disease (COPD) and healthy participants recorded occurrence of respiratory-symptom related doctor visits (n = 1,048) in one to six four-week intervals over two years. For each disease subgroup, odds ratios (ORs) for doctor visit were estimated as a function of NO2 or TSP concentrations (per 10 micrograms per cubic meter [µg/m3]) lagged between 0–13 days in a polynomial distributed lag model. RESULTS: Higher ORs for NO2 in participants with COPD (OR: 1.17, 95%CI: 1.02–1.35) and asthma (OR: 1.15, 95%CI: 1.02–1.30) occurred at exposure lags of two and five days, respectively. Doctor visits increased by 9.1% (95%CI: 3.2–15.4%) and 4.2% (95%CI: 1.2–7.2%) over the first week following a 10 µg/m3 increase in NO2 concentration in the COPD and chronic bronchitis subgroups, respectively. The percent increase in the COPD subgroup was significantly greater (p <0.05) when compared with the healthy subgroup. Observed findings were similar for TSP. CONCLUSIONS: Respiratory problems leading to a doctor visit, associated with an increase in exposure to NO2 and TSP, may have a faster dynamic in individuals with COPD.